2012
DOI: 10.1002/jbio.201100080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for noninvasive determination of carotenoids in human and animal skin: Raman spectroscopy versus reflection spectroscopy

Abstract: Based on compelling in vivo and in vitro studies on human skin, carotenoids are thought to be of great interest as powerful antioxidants acting to prevent free-radical-induced damages, including premature skin ageing and the development of skin diseases such as cancer. Among the available techniques that are suitable for noninvasive determination of carotenoids in human skin, are resonance Raman spectroscopy (RRS) and reflection spectroscopy (RS). For RS, a LED-based miniaturized spectroscopic system (MSS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 72 publications
0
57
2
1
Order By: Relevance
“…The hand palm was chosen due to its accessibility, the absence of strong pigmentation variations, which can influence measurements, and the proven reliability and reproducibility of measurement results in previous studies [21]. The used measurement system is based on reflectance spectroscopy [35] (Opsolution GmbH, Kassel, Germany) containing an optical window on the undersurface. The radiation of LED emits in the maximum of the absorption spectrum of the carotenoids at 465 ± 25 nm, whereas another LED emits beyond this absorption spectrum to determine the background signals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hand palm was chosen due to its accessibility, the absence of strong pigmentation variations, which can influence measurements, and the proven reliability and reproducibility of measurement results in previous studies [21]. The used measurement system is based on reflectance spectroscopy [35] (Opsolution GmbH, Kassel, Germany) containing an optical window on the undersurface. The radiation of LED emits in the maximum of the absorption spectrum of the carotenoids at 465 ± 25 nm, whereas another LED emits beyond this absorption spectrum to determine the background signals.…”
Section: Methodsmentioning
confidence: 99%
“…Carotenoids were measured as marker substances for the antioxidant status of the human skin [35,36]. It has been shown that antioxidative substances form protective chains in the skin, protecting each other from the destructive effects of free oxygen species [36].…”
Section: Methodsmentioning
confidence: 99%
“…Results are displayed as a value ranging from 1 to 12, expressed in arbitrary units. The skin scanner device was previously described in detail by Darvin et al [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was demonstrated that the carotenoids could represent marker substances for the whole antioxidant status of human and animal skin [23]. Recently, a skin scanner was presented which permits the qualitative and quantitative determination of carotenoid concentration in human skin non-invasively by reflectance spectroscopy [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, corresponding devices have been developed allowing the quick noninvasive determination of carotenoids in the skin [27,28]. …”
Section: Introductionmentioning
confidence: 99%